Faktor-faktor yang mempengaruhi pemindahan latihan : satu kajian kes - Christopher Nizam, Lim Bugau. (Universiti Malaysia Sarawak, (UNIMAS), 2003)
This study aimed to investigate thefactors that influence the effectiveness ofQuality Work Group III Malaysia LNG Stln Bhd. The survey method through a questionnaire was used 10 obtain the findings of dIis study. The respondents consist of 35 staff who have aI/ended the Quality Work Group trailling. The qwstionnaire used in this study is divided into three sections, Section A: respondents ' background, Section B: level ofthe transfer ofQuality Work Group Training and Section C: factors that influence the transfer ofQualily Work Group Training. The data was analyzed using the Statistical Packagefor Social Sciences (SPSS). Pearson Correlation Test and Multiple Regression Analysis were used to test the hypotheses. The brtp/ication ofthis study can help the organization to identify the factors that influence the transfer of Quality Work Group Training. This study wouid also provide the opportunity for future researchers to lItcrease the scope o/ research pertaining to the transfer oftraining.